2017
DOI: 10.1002/smr.1847
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term growth rate of evolving software: Empirical results and implications

Abstract: The amount of code in evolving software-intensive systems appears to be growing relentlessly, affecting products and entire businesses. Objective figures quantifying the software code growth rate bounds in systems over a large time scale can be used as a reliable predictive basis for the size of software assets. We analyze a reference base of over 404 million lines of open source and closed software systems to provide accurate bounds on source code growth rates. We find that software source code in systems dou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…One of the most popular ways to study software evolution focuses on the growth of the source code. Hatton et al conducted the largest study to date on software growth rate; specifically they studied the growth rate of over 404 million lines of both open source and proprietary software and concluded that code doubles about every 42 months [6]. Similarly, a large study on 6000 open source systems by Koch [7] revealed that while the mean growth is linear, there is a significant percentage of systems with super-linear growth.…”
Section: Software Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the most popular ways to study software evolution focuses on the growth of the source code. Hatton et al conducted the largest study to date on software growth rate; specifically they studied the growth rate of over 404 million lines of both open source and proprietary software and concluded that code doubles about every 42 months [6]. Similarly, a large study on 6000 open source systems by Koch [7] revealed that while the mean growth is linear, there is a significant percentage of systems with super-linear growth.…”
Section: Software Evolutionmentioning
confidence: 99%
“…The First Research Edition (November 3, 1971 6 ) was a rewrite of the PDP-7 Unix targeting the PDP-11 processor. The following architectural design decisions are visible in this edition.…”
Section: First Research Editionmentioning
confidence: 99%
“…A recent empirical study [25] has calculated the compound annual growth rate of over 4000 software projects, including popular FOSS products as well as closed source ones. This rate is sensibly in the range of 1.20-1.22, corresponding to a doubling in size every 42 months.…”
Section: Growth Of Public Source Code (Rq3)mentioning
confidence: 99%
“…To answer this question we perform an extensive study of the Software Heritage archive, continuing a long tradition of software evolution studies [10,12,25,26,35], which we extend here by several orders of magnitude and perform over a period of more than 40 years. We show evidence of a remarkably stable exponential growth rate of original commits and files over time.…”
Section: Introductionmentioning
confidence: 99%
“…4 For what it is worth, if we had maintained this monthly growth rate for a year, we would have ended with a 20% growth rate over 12 months, as many others have found. 5…”
Section: Software Solution and Architecturementioning
confidence: 99%